Peran Guru PAI Dalam Membangun Moderasi Beragama Di Sekolah Menengah Kejuruan (SMK) T. Amir Hamzah Indrapura - Arfandi Setiawan; Mei Sandi Pasaribu; Rizka Harfiani (Maslahah: Jurnal Pengabdian Masyarakat, 2023)
The purpose of this study was to describe the role of the PAI teacher and find out the supporting and inhibiting factors of the PAI teacher in building religious moderation in the Private Vocational High School (SMK) T. Amir Hamzah Indrapura. This study uses a quantitative research method, which is a method that relies on objective measurement and statistical mathematical analysis of sample data obtained through questionnaires, opinion polls, tests, or other research instruments to prove or test hypotheses (temporary allegations) proposed in the study. The values of religious moderation built by PAI teachers are: tolerance, respect and respect for others, caring for others, being fair, obeying rules, non-violence and national commitment, providing an understanding of religious moderation values such as fairness. Supporting factors include: support from school principals, PAI teachers who are given sufficient knowledge with religious moderation training activities. The inhibiting factor is the students themselves because of the lack of understanding of students about religious moderation and there are some students who show bad behavior in establishing harmony in religion at school.